Números naturais e fracionários: aspectos históricos, operações e bases numéricas - Souza, Luiz Carlos de (2020)
One of Profmat's objectives is to provide solid mathematical training for the development of teaching in Basic Education. Thus, in this dissertation, we present a historical rescue on counting, numbering system, a simple classification of the numbering system and numbering systems of some ancient peoples, different types of the algorithm for the four operations (addition, subtraction, multiplication, and division), historical context on fractions, history of addition algorithms for positional systems, highlighting the improvement of numbers and calculations over the years. To draw teachers 'attention to students' difficulties in understanding operations on the decimal basis, we applied the operations on bases 5 and 6 and presented discussions on parity, prime numbers, MMC, and fractions in other numbering bases. In the end, we briefly discussed the need for students in the initial grades to have contact with other numbering bases.